Evaluasi Potensi Kawasan Kotagede Sebagai Destinasi Wisata Berbasis Warisan Budaya (Heritage Tourism)Daerah Istimewa Yogyakarta - Dwi Handayani, Gretta, Dr.Kuswaji Dwi Priyono, M.Si (2016)
ABSTRACT The heritage tourism is a special interest tour by seeing culture and local wisdom. The heritage tourism can be applied in the region where still have a cultural heritage. Kotagede is really potential to be a first class heritage tourism destination. This research aims : (1) to evaluate the potency of heritage tourism destination in research area, (2) map the distribution layout object and (3) analyzing the direction of development in the study area. The method used is a survey method, potential analysis and SWOT analysis. The result of this research shows three (3) classes of tourism potency: high, medium, and low. The highest potential is owned by Kompleks Makam Kotagede and Omah Dhuwur Restaurant. The medium potential is owned by seven objects: Perajin Perak Basen, Perpustakaan Kotagede, Omah Joglo UGM, Watu Gilang and Gatheng, Between Two Gates, Masjid Kotagede and Pasar Kotagede. The lowest potential is occupied by Benteng Cepuri. Manufacture Distribution map the location of sights of cultural heritage in Kotagede, as well as on the direction of development in Kotagede include: optimization area parking space, optimization special vehicles from area parking space to the location of an object, make the region as a walk city, pack a package of tourist visits in accordance travel interests, and optimizing facilities and infrastructures heritage tourism cooperation between the government and the public to preserve the cultural heritage objects. Keyword : Heritage Tourism, Kotagede, Tourism Potency